ANALISIS FRAMING PEMBERITAAN KERUSUHAN PASCA PEMILU 2019 PADA MAJALAH TEMPO EDISI SENIN, 10 JUNI 2019 - Pradnyandari, Ni Kadek Sri Rejeki; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2020)
Tempo magazine’s coverage of Team Mawar, who is suspected of being the mastermind behind the post-20 election riots has attracted a lot of media attention. In order to analyze this, the researcher used the Pan and Kosicki framing analysis method. This research focuses on reporting on post-election riots in 2019. In this study, researchers used the Monday, June 10, 2019 edition of Tempo magazine as the unit of analysis. The results of this study is news framing by Tempo magazine is carried out by among others; selecting news sources, selecting quotations from news sources, using pronouns, repeating word and placing images that can support news framing. Key words: Framing , Tempo, 2019 Post-Election Riots .